Grammatical processing in two languages: How individual differences in language experience and cognitive abilities shape comprehension in heritage bilinguals - Bice, Kinsey; Kroll, Judith F. (Journal of neurolinguistics, 2021)
Recent studies have demonstrated variation in language processing for monolingual and bilingual speakers alike, suggesting that only by considering individual differences will an accurate picture of the consequences of language experience be adequately understood. This approach can be illustrated in ERP research that has shown that sentence contexts that traditionally elicit a P600 component in response to a syntactic violation, elicit an N400 response for a subset of individuals. That result has been reported for monolingual speakers processing sentences in their L1 and also for bilinguals processing sentences in their L2. To date, no studies have compared variation in L1 and L2 ERP effects in the very same bilingual speakers. In the present paper, we do that by examining sentence processing in heritage bilinguals who acquired both languages from early childhood but for whom the L2 typically becomes the dominant language. Variation in ERPs produced by the non-dominant L1 and dominant L2 of heritage bilinguals was compared to variation found in monolingual L1 processing. The group-averaged results showed the smallest N400 and P600 responses in the native, but no longer dominant, L1 of heritage bilinguals, and largest in the monolinguals. Individual difference analyses linking ERP variation to working memory and language proficiency showed that working memory was the primary factor related to monolingual L1 processing, whereas bilinguals did not show this relationship. In contrast, proficiency was the primary factor related to ERP responses for the no longer dominant L1 for bilinguals, but unrelated to monolingual L1 processing, whereas bilinguals’ dominant L2 processing showed an intermediate relationship. Finally, the N400 was absent for bilinguals performing the task in the same language in which they initially learned to read, but significantly larger when bilinguals performed the task in the other language. The results support the idea that proficient bilinguals utilize the same underlying mechanisms to process both languages, although the factors that affect processing in each language may differ. More broadly, we find that bilingualism is an experience that opens the language system to perform fluidly under changing circumstances, such as increasing proficiency. In contrast, language processing in monolinguals was primarily related to relatively stable factors (working memory). •We assessed individual differences in ERP responses to grammatical violations.•Heritage bilinguals had smaller ERP effects in their less-dominant L1.•Working memory modulated ERP responses in monolinguals.•Proficiency modulated ERP responses in both bilinguals' languages.•Early reading experience affected the bilinguals' N400.